2011
DOI: 10.1002/hyp.8149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigation withdrawals on streamflows in a karst environment: lower Flint River Basin, Georgia, USA

Abstract: Abstract:Extensive implementation of centre pivot irrigation systems occurred between 1970 and 1980 in the lower Flint River Basin (FRB) of southwestern Georgia, USA. Groundwater within this karstic system is in direct hydraulic connection with regional streams, many of which are incised through the overburden into underlying limestone. We used long-term U.S. Geological Survey gaging station data to evaluate multiple flow metrics of two tributaries (Ichawaynochaway Creek and Spring Creek) in the lower FRB to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…In contrast, the two severe droughts that have occurred in the LFRB since 1999 appear to be more indicative of long-term climatic conditions in Georgia (Cook et al, 1999). Perhaps more importantly, contemporary droughts are compounded by the effects of agricultural water withdrawals (Rugel et al, 2012). Indeed, recent work in a small Chattahoochee River tributary indicated that increased levels of water use may contribute to an increased risk of population extinction for three imperilled freshwater mussel species .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the two severe droughts that have occurred in the LFRB since 1999 appear to be more indicative of long-term climatic conditions in Georgia (Cook et al, 1999). Perhaps more importantly, contemporary droughts are compounded by the effects of agricultural water withdrawals (Rugel et al, 2012). Indeed, recent work in a small Chattahoochee River tributary indicated that increased levels of water use may contribute to an increased risk of population extinction for three imperilled freshwater mussel species .…”
Section: Discussionmentioning
confidence: 99%
“…The mussel collection data were used to develop predictive models of species occupancy for 21 freshwater mussel species native to the LFRB. in many LFRB tributaries since the implementation of intensive irrigation in the 1970s (Rugel et al, 2012). Additionally, the LFRB has experienced two severe and prolonged droughts since 1999 (NCDC, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While few dams are on the Flint River, it is at the forefront of a multistate controversy regarding competing water uses (Jones, 2008). Water withdrawals for both municipal and agriculture uses have significantly lowered streamflows throughout the basin (Rugel et al, 2012), which could affect the ability of migratory fishes such as shoal bass to reach preferred spawning grounds (Northcote, 1997). The consequences of losing migratory forms of species while retaining the resident forms is unknown, but potentially catastrophic to long-term species persistence (Northcote, 1997;Nelson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the research in this area has focused on streams in arid and semi-arid environments [85,86], the same trends have been observed in streams of mesic environments with porous substrata, for example karstic systems [87]. Factors related to stream hydrology are among the most important determinants of the resulting communities and can even impact riparian trees [88].…”
Section: Impacts Of Agricultural Expansionmentioning
confidence: 99%